2019
DOI: 10.7783/kjmcs.2019.27.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catechin-rich Green Tea Extract on the MMP-1 Activity of HaCaT Keratinocyte Cells and on UVB-induced Skin Damage in Hairless Mice

Abstract: Background: Skin is an organ that protects the human body from various environmental stimuli that can induce immune system activation. Skin aging can be largely divided into two categories: physiological aging, which is caused by the a decreased physiological function of the skin and structural changes with aging, and photoaging, which is caused by the chemical stress induced by external stimuli such as ultraviolet (UV) radiation. Methods and Results: The objective of this study was to investigate the anti-wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…MMP-1 is closely related to human skin aging, and its over-expression negatively affects skin health. Studies have shown that catechins can inhibit MMP-1 activity, thereby protecting the skin (38). (−)-Catechin gallate possesses a good antioxidant effect and promoting cell transport (39).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 is closely related to human skin aging, and its over-expression negatively affects skin health. Studies have shown that catechins can inhibit MMP-1 activity, thereby protecting the skin (38). (−)-Catechin gallate possesses a good antioxidant effect and promoting cell transport (39).…”
Section: Discussionmentioning
confidence: 99%
“…According to Wagn et al, when combined with YAG laser, catechin can reduce wrinkles and pigmentation, increase collagen, and enhance SOD activity in the skin of photodamaged mice [ 233 ]. Catechins isolated from green tea and elm root bark can inhibit MMP-1 expression and may have antiaging effects on fibroblasts, HaCaT cells, and mice [ 164 , 165 , 166 , 167 ]. Green tea catechins were found to prevent skin cellular senescence by regulating NF-κB, AP-1, and MAPK signaling pathways [ 164 ].…”
Section: Therapeutic Potential Of Plant Polyphenolsmentioning
confidence: 99%